Timely Topics - Schlesinger, G. author. aut Link
XI, 230 p.
Keywords: The non-technical, basic yet familiar features of time are investigated, e.g. two novel, detailed arguments defending the common view that 'time rolls relentlessly' are advanced; a number of hitherto neglected fundamental differences between spatio-temporal location and every other physical property are discussed; the unresolved problem, why the past is so much better known than the future is tackled. For those who wish to delve deeper, 25% of the book consists of problems to ponder and their possible solutions.